Reducing ICU Length of Stay: The Impact of a Multidisciplinary Perioperative Pathway in Vestibular Schwannoma - Yawn, Robert J.; Nassiri, Ashley M.; Harris, Jacqueline E.; Manzoor, Nauman F.; Godil, Saniya; Haynes, David S.; Bennett, Marc L.; Weaver, Sheena M. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective This study was aimed to evaluate the impact of a multidisciplinary perioperative pathway on length of stay (LOS) and postoperative outcomes after vestibular schwannoma surgery.Setting This study was conducted in a tertiary skull base center.Main Outcome Measures The impact of the pathway on intensive care unit (ICU) LOS was evaluated as the primary outcome measure of the study. Overall resource LOS, postoperative complications, and readmission rates were also evaluated as secondary outcome measures.Methods Present study is a retrospective review.Results A universally adopted perioperative pathway was developed to include standardization of preoperative education and expectations, intraoperative anesthetic delivery, postoperative nursing education, postoperative rehabilitation, and utilization of stepdown and surgical floor units after ICU stay. Outcomes were measured for 95 consecutive adult patients who underwent surgical resection for vestibular schwannoma (40 cases before implementation of the perioperative pathway and 55 cases after implementation). There were no significant differences in the two groups with regard to tumor size, operative time, or medical comorbidities. The mean ICU LOS decreased from 2.1 in the preimplementation group to 1.6 days in the postimplementation group (p = 0.02). There were no significant differences in overall resource LOS postoperative complications or readmission rates between groups.Conclusion Multidisciplinary, perioperative neurotologic pathways can be effective in lowering ICU LOS in patients undergoing vestibular schwannoma surgery without compromising quality of care. Further research is needed to continue to sustain and continuously improve these and other measures, while continuing to provide high-quality care to this patient population.
Keywords: quality; vestibular schwannoma; acoustic neuroma; pathway; multidisciplinary; skull base surgery; translabyrinthine; suboccipital; retrosigmoid